2D Optical Waveguides Based on Hierarchical Organic Semiconductor Single Crystals. Issue 22 (18th September 2021) - Ma, Yingxin; Zong, Yi; Yin, Huiling; Lin, Hongtao; Chen, Shuhai; Wang, Xue‐Dong
Abstract: Toward the evolution of integrated optoelectronic circuits, it is vital matter to realize 2D optical waveguide at micro/nanoscale. However, due to the waveguiding principle of the traditional dielectric waveguide, the transverse and longitudinal dimensions cannot be greatly reduced, thus the size of photonic apparatus is far from reaching the size level for the microelectronic device. Therefore, it is difficult to achieve a high‐level hybrid integration of integrated optical path and microelectronic circuit. However, the organic crystals with polygonal structure and hierarchical structure as the medium also can form optical waveguide by confining photons/electrons at the micro/nanoscale along different directions, and these organic microcrystals can be well applied into the ultracompact optoelectronic devices. Herein, the fabrication of organic crystals as the medium of 2D optical waveguide is briefly introduced, as well as the 2D optical waveguide phenomenon existing in these polygonal and hierarchical microcrystals. Moreover, a conclusion is drawn and expectations are expressed for the 2D optical waveguide based on organic microstructure in the near future. Abstract : 2D optical waveguides which are confined into polygonal microcrystals and hierarchical microcrystals at micro/nanoscale have great significance in the optoelectric field due to their isotropic and anisotropic transmission properties. Herein, the recent development of 2D optical waveguides in microcrystals is reviewed. The prospects and suggestions for future development are presented.